Skeleton bobsleigh mechanics : athlete-sled interaction - Roberts, I. J. M. (University of Edinburgh, 2013)
Skeleton is one of the three Olympic sporting disciplines to be held in the manmade bobsleigh tracks. The sport of skeleton uses a one-man sled, on which the athlete travels headfirst down a mile long track reaching speeds of up to 147 km/h. As with many sports the engineering of the equipment is playing a greater role in the overall performance of the athlete. Although the sled alone cannot win medals a poor choice of equipment can be the difference between winning and losing. The primary focus of this research is on the trajectory and response of the sled frame and how these relate to athlete perception during a descent and overall performance. Sleds were instrumented with accelerometers and strain gauges that enabled the mechanical behaviour of the sled to be determined quantitatively. Qualitative data comprised of athlete training logs (mainly from the author), provided information about the feel and perception of the run. Tests were made on whole tracks, dedicated push-tracks and in the laboratory. In addition this PhD has touched on aerodynamics and runner-ice interaction. The thesis is split into three main sections: (1) The initial push phase of a descent was investigated at the Torino Sliding Centre and Calgary Olympic Park with a sled instrumented with an accelerometer. Using a single axis in the forwards direction of the sled determined the sensitivity of the measuring and acquisition device along with the capabilities and quality of information gained. Through analysis it is possible to identify the dynamics that occur during a push start and how to interpret them in order to improve athlete performance during the push start. (2) A whole descent at the Koenigssee International Race Track was measured using a three axis accelerometer. The dynamics at specific track locations were examined in detail and linked with athlete perception. Comparison of multiple descents enables the sled trajectory to be quantified to determine the overall success of the resultant trajectory. This analysis shows there is scope for maximizing athletic performance in conjunction with quantitative instrumentation of the equipment. (3) Complete descents at the Lake Placid Olympic Park were made on a sled instrumented with rosettes of strain gauges. The strain gauges were calibrated in the laboratory. Analysis of strain gauge data from the track showed the extent of deformation of the frame upon entering and exiting curves and while under the g-forces experienced, again this data is compared with athlete perception. Consideration is briefly given as to how these dynamic measurements can be used to evaluate current and future frame designs